STRATEGI REKRUTMEN PARTAI KEADILAN SEJAHTERA YOGYAKARTA - AHMAD ANFASUL MAROM (Al Qalam, 2011)
Nowadays, recruitment becomes a serious problem for political party reform in Indonesia. We have witnessed many instant cadres who lacked competence but easily obtained a position. Apparently, this issue has become a trend among parties causing the party function to change into broker such as Out Sourching Company. Before the cadres were engaged in political activities, they were already known in the public space such as celebrities, rich men, and elite families. By this context, we need to pay attention toward this phenomenon because from this point the policy makers are made. This paper will highlight the recruitment process of Prosperous and Justice Patry (PKS) in Yogyakarta. The time setting is after 2009 Election. There are two research questions that will be discussed here: First, what kind of strategies do PKS use in recruiting their cadres? Second, how do they select their cadre to be placed in strategic positions (party, executive, legislative)? Furthermore, this paper will adopt some theories of recruitment to examine the PKS's political party typology. Keywords: Islamic party, Prosperous and Justice Party (PKS), Yogyakarta